Rewrite the right side as √3/3 = 1/√3, and recall that tan(x) = 1/√3 when x = π/6. Then since tan is π-periodic, taking the inverse tan of both sides gives
![\tan\left(x + \frac\pi3\right) = \frac1{\sqrt3} \implies \tan^(-1)\left(\tan\left(x + \frac\pi3\right)\right) = \tan^(-1)\left(\frac1{\sqrt3}\right) + n\pi](https://img.qammunity.org/2023/formulas/mathematics/college/ic9nclp2xmkwuehcwrmqdekl42fk1dcc6y.png)
![\implies x + \frac\pi3 = \frac\pi6 + n\pi](https://img.qammunity.org/2023/formulas/mathematics/college/u44bx5afqlshwga2o5pllicqmcpi8v8vlg.png)
where n is any integer. Solving for x, we get
![x = -\frac\pi6 + n\pi](https://img.qammunity.org/2023/formulas/mathematics/college/m35s2hdj50ziqth6mtccygte62ucicwykw.png)
and the solutions in the interval [0, 2π] are x = 5π/6 and x = 11π/6 (for n = 1 and n = 2).